Pós-tratamento físico-químico de efluente sanitário para remoção de fósforo - Baccarin, Lindsay Iara Pegoraro (2011)
The wastewater, even after primary and secondary treatment, may contain organic matter and nutrients such as phosphorus. Which are causing negative impact when released in water body receptors by their accumulation in the aquatic environment, interfering with the natural biological cycle. In this context, alternative effluent technologies are being extensively studied such as physical-chemical processes including coagulation followed by flocculation and subsequent sedimentation as post-treatment of effluents before their discarding in water body receptors. The main goals of this work were quantification of different forms of phosphorus and the study of physical-chemical treatment by flocculation and sedimentation using inorganic salts (ferric chloride, aluminum sulfate, calcium oxide and calcium chloride), as an alternative after the conventional biological treatment, in the wastewater sanitary ETE of the Passo Fundo University. The results showed that the soluble phosphorous forms are the main forms in the final sanitary effluent. The quantification of these different phosphorous fractions facilitates the evaluation of each coagulant agent used in the different concentrations. The ferric chloride at concentration of 250 mg/L showed the best total phosphorous remotion taxes. At this concentration the total phosphorous concentration decreased from 16 mg/L to 3 mg/L after the treatment. The aluminum sulfate showed efficiency similar to ferric chloride. The minimization of the organic matter and nutrients suchas phosphorous at the sanitary effluent by use of this post treatment will contribute with a less impacting effluent deposition.